Single Curvature Bending Results of Structural Stitched Textile Reinforcements Part II: Quantitative Analysis Using Taguchi Method (The International Journal of Engineering & Information Technology (IJEIT), 2024)
A Novel non-crimp dry thick fabric was manufactured at the University of Ottawa advanced preforming technology (uOttawa fabric) to cover the growing need for such thick preforms in the aerospace applications. The bending behavior was investigated using significant numbers of tests performed with a new bending apparatus designed and manufactured at University of Ottawa.This research paper was aimed to analyze the bending results obtained for samples made from the new uOttawa fabric and samples made from an industrial fabric using a statistical method celled Taguchi method. The Taguchi analysis highlights the most parameters having the stronger effects on testing. The main parameters investigated in bending were the type of fabric, the thickness, yarn orientations, fibre volume fraction and bending cycles. Two plans were used to investigate which parameters have strong effect on bending moment. The Taguchi analysis revealed that the type of fabric, number of cycles and fibre volume fraction have the largest effect on bending behavior of these fabrics.